Agency The Entrepreneurial Self in Narratives of Transformation: Debuting in the Literary Field at the Dawn of the Twenty-First-Century - Fischer, Jessica (Königshausen & Neumann, 2020)
Which forms of agency does literature offer to the reader in the twenty-first century? This study investigates migrant lives in contemporary fiction published by young British Asian writers. Examining the protagonists' ideas of ›success‹ in becoming a full member of their society, Jessica Fischer carves out the naturalised model of homo economicus in these texts and in contemporary fiction more generally. She draws attention to the enterprising self as the preferred subject in today's hegemonic discourses and postulates a new conceptualisation of ›agency‹. This book offers an interdisciplinary approach to narratives of transformation. Moreover, it is an urgently needed combination of cultural and postcolonial studies that tackles ethical questions concerning the normative construction of the subject in identity politics.